Developing an edible food product from tender coconut mesocarp and analyzing its sensory parameters - Kalina, S; Navaratne, S.B (My University, 2018)
Coconut (Cocos nuciferus. L) Is one of the perennial tree crop widely grown in many South East Asian countries. The parts of coconut such as epicarp, mesocarp and endocarp were considered inedible. The present study is aimed at developing a food product from mesocarp. For this, four types of edible snacks were produced from, tender young and king coconut mesocarps by providing a combination of optimum treatments such as blanching - solar drying and blanching - cooling with dehumidifying, and a sensory evaluation was done for snacks based on the parameters such as aroma, colour, taste, bitterness, sweetness, texture, mouth feeling and overall acceptability. The results of sensory evaluation reveals that, there is a significant difference in taste, bitterness, sweetness and overall acceptability of coconut mesocarp snacks developed, at 95% confidence level and among the snacks produced, King coconut blanched-solar dried mesocarp snack is more sensory appealing based on the average ranks of these significant sensory parameters. So, a consumer preferable edible food product could be produced from King Coconut blanched-solar dried mesocarp.
Keywords: King coconut, Young coconut, Mesocarp, Sensory parameters